Human Rights are attained through struggle: Racial equality, judicial activism and the defense of collective causes in the south of Brazil - Rios Petraca, Fernanda (Política. Revista de Ciencia Política, 2011)
This article analyzes the relation between the defense of collective causes related to race and professional performance based on judicial expertise in southern Brazil. It focuses on a group of lawyers who act professionally in defense of racial equality in Rio Grande do Sul. The article empirically examines the emergence of racial rights in Brazil and lawyers who defend “racial causes”. Moreover, the article analyzes the different modes of association between professional intervention and militant commitment, by examining the lawyers’ social and political trajectories. The methodology consisted of biographical interviews with “militant professionals” and analysis of secondary sources. This study demonstrates that ethnic-racial identity and political commitment are fundamental elements in the formation of professional conceptions.